2023
DOI: 10.1126/sciadv.adh2694
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced sub-1 eV detection in organic photodetectors through tuning polymer energetics and microstructure

Abstract: One of the key challenges facing organic photodiodes (OPDs) is increasing the detection into the infrared region. Organic semiconductor polymers provide a platform for tuning the bandgap and optoelectronic response to go beyond the traditional 1000-nanometer benchmark. In this work, we present a near-infrared (NIR) polymer with absorption up to 1500 nanometers. The polymer-based OPD delivers a high specific detectivity D * of 1.03 × 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…Organic photodetectors (OPDs) with specific responses in the near-infrared (NIR) region offer unique potential for applications such as remote control of intelligent and portable electronic devices, night surveillance, biomedical monitoring, and image sensing. However, the limited availability of molecular materials suitable for NIR-OPDs poses a challenge, as superior narrow bandgap organic semiconductors are required to ensure efficient charge generation and NIR response. Historically, significant efforts have been made in the development of p-type polymer donors with NIR light absorption for NIR-OPDs due to the limited tunability of fullerene acceptors in chemical structures. ,, However, the emergence of nonfullerene acceptors (NFAs) in recent years has revolutionized the field of NIR organic semiconductors due to the fact that NFAs can offer tunable optical bandgaps, energy levels, and molecular crystallinity. , In 2015, Zhan et al reported the development of ITIC, an donor–acceptor–acceptor (A–D–A) type fused-ring electron acceptor with absorption onset approaching 800 nm . This accomplishment marks a significant milestone in the advancement of narrow bandgap organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…Organic photodetectors (OPDs) with specific responses in the near-infrared (NIR) region offer unique potential for applications such as remote control of intelligent and portable electronic devices, night surveillance, biomedical monitoring, and image sensing. However, the limited availability of molecular materials suitable for NIR-OPDs poses a challenge, as superior narrow bandgap organic semiconductors are required to ensure efficient charge generation and NIR response. Historically, significant efforts have been made in the development of p-type polymer donors with NIR light absorption for NIR-OPDs due to the limited tunability of fullerene acceptors in chemical structures. ,, However, the emergence of nonfullerene acceptors (NFAs) in recent years has revolutionized the field of NIR organic semiconductors due to the fact that NFAs can offer tunable optical bandgaps, energy levels, and molecular crystallinity. , In 2015, Zhan et al reported the development of ITIC, an donor–acceptor–acceptor (A–D–A) type fused-ring electron acceptor with absorption onset approaching 800 nm . This accomplishment marks a significant milestone in the advancement of narrow bandgap organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…12 Many different NIR-absorbing organic small molecule and polymer compounds have been prepared and some of these have been proven to be useful for NIR organic photodetectors (OPDs) in a wavelength range inaccessible for silicon. 13–19 However, for each targeted wavelength (range), new molecules have to be developed, which is a very time consuming and costly process.…”
Section: Introductionmentioning
confidence: 99%
“…There are ongoing efforts to develop alternative semiconductors that facilitate low-cost, monolithic detector fabrication. Among these emerging technologies, organic semiconductors such as donor–acceptor conjugated polymers enable facile and scalable processing and functionality to infrared wavelengths beyond 1 μm. However, according to the energy-gap law, as the bandgap of organic semiconductors decreases, the recombination rate of photogenerated excitons increases, leading to a decline in device efficiency at longer wavelengths.…”
Section: Introductionmentioning
confidence: 99%